Bernard of Clairvaux : Monastic Sermons - Bernard, of Clairvaux, Saint, 1090 or 1091-1153 (Book collections on Project MUSE., 2016)
Saint Bernard was born in 1090 near Dijon, France. He joined the fifteen-year-old monastery of Cîteaux in 1113. In 1115 he became the founding abbot of Clairvaux Abbey, whence his name, Bernard of Clairvaux. Saint Bernard was a gifted and prolific writer of theological treatises, Scriptural commentaries, letters, and many sermons. The sermons in the collection published here, styled Sermones de diversis (Sermons about Various Topics), lack the specific point of departure that characterizes his other sermons. That is, whereas the sermons on the Song of Songs are a verse-by-verse commentary on that biblical book and his Sermons for the Year follow the liturgical calendar, this collection of sermons deals with his various pastoral concerns. Since Scripture is always Bernard's point of departure and inspiration, the sermons often read like a Scripture study, but what comes through equally is the voice of an understanding spiritual father who is a masterful student of Scripture.